Metamorphism as the cause of bone alteration in the Jarrow assemblage (Langsettian, Pennsylvanian) of Ireland. (7th December 2022) - Gogáin, Aodhán Ó; O'Sullivan, Gary; Clements, Thomas; Hoare, Brendan C.; Murray, John; Wyse Jackson, Patrick N.
Abstract: The Jarrow assemblage is a Lagerstätte of Pennsylvanian tetrapods and fish preserved in the Leinster Coalfield, Ireland. Fossils from this site have an interesting taphonomy that is not observed in other Pennsylvanian coal swamp assemblages. Jarrow tetrapod bone material has undergone alteration and eventual coalification, causing specimens to become poorly defined from the surrounding coal matrix. Bone alteration at Jarrow has traditionally been linked to early diagenesis. A multi‐analytical approach, combining x‐ray scanning electron microscopy, cathodoluminescence, micro computed tomography and laser ablation quadrupole inductively coupled plasma mass spectrometry, was used to investigate the origin of alteration within the Jarrow fossil specimens. Original bone morphology is no longer present, being replaced by bituminous material and sphalerite surrounded by tabular apatite (a morphology atypical of bone apatite). Direct U–Pb dating of this recrystallized apatite provides an age of 302.03 ± 11.38 Ma. In this recrystallized apatite, core‐to‐rim variation in halogen elements, variably positive and negative Eu‐anomalies and depletion in light rare earth elements (REEs) suggest an influence of hydrothermal fluids sourced during the maturation of the Leinster Coalfield. A new taphonomic model for the Jarrow assemblage is proposed: alteration of primary fossil bone occurred primarily due to burial heating of the Leinster Coalfield caused by Variscan deformation. Bone apatite was dissolved and subsequently recrystalized as tabular crystals, probably concurrent with mineralization of sphalerite and during coalification, giving the Jarrow assemblage fossils their unique appearance.